The influence of sufficiency economy philosophy practice on SMEs' performance in Thailand - Muttanachai Suttipun; Afsa Arwae (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to investigate the extent and level of sufficiency economy philosophy (SEP) practice, the performance measured by the balanced scorecard (BSC) of small and medium-sized enterprises (SMEs) in Thailand, and to test the influence of SEP practice on SMEs' performance measured by BSC. Research Design & Methods: Using stratified sampling, 600 SMEs were adopted as the sample in this study. Self-reported data was collected using a mailed questionnaire containing items incorporating a five-point Likert scale. The data was initially analysed by descriptive analysis, correlation matrix, and multiple regression. Findings: The study found that both SEP practice and performance measured by the BSC of SMEs were at a high level. Moreover, the moderation element was the most common SEP practice followed by the morality condition, the reasonableness element, the self-immunity element, and the knowledge condition. The multiple regression analysis indicated that all the elements and conditions of SEP positively and significantly influenced performance measured by the BSC. Using control variables, the study also found the significant relationship between firm size, firm age, and SMEs' performance. Implications & Recommendations: Business owners and top management can use SEP as a practical management tool with which to operate their business instead of adopting Western management models. Contribution & Value Added: The study findings can demonstrate that stakeholder theory can be used to explain SMEs in Thailand putting SEP into practice in order to satisfy stakeholder demands for better performance.
Keywords: M10; M40; M41; N15; D41; D43; E58; G18; G21; 330; Sufficiency economy philosophy; performance; balanced scorecard; small and medium enterprises; Thailand